Assessing the knowledge level, attitudes, risky behaviors and preventive practices on sexually transmitted diseases among university students as future healthcare providers in the central zone of Malaysia: a cross-sectional study - Folasayo, Adigun Temiloluwa; Oluwasegun, Afolayan John; Samsudin, Suhailah; Saudi, Siti Nor Sakinah; Osman, Malina; Awang Hamat, Rukman (Multidisciplinary Digital Publishing Institute, 2017)
This study was done to assess the knowledge, attitudes, risky behaviors and preventive practices related to sexually-transmitted diseases (STDs) among health and non-health sciences university students as future healthcare providers in Malaysia. A total of 700 health and non-health sciences university students (255 male; 445 female) aged between 17 and 30 years were surveyed by using a self-administered questionnaire. The majority (86.6%) had heard of STDs, and 50.4% knew STDs could present without symptoms. HIV remains the best known STD (83.6%) by the students, while chlamydia (26%) and trichomoniasis (21.0%) were rarely known. Gender, age group, educational level and faculty type were strongly associated with knowledge level (p-values < 0.05). Most of them (88.8%) were aware that STD screening was important while use of condoms was protective (63.8%). The majority of them strongly felt that treatment should be sought immediately if they (85.5%) and their partners (87.4%) have symptoms. Among the sexually-active students, 66.7% and 18% had sexual intercourse with multiple partners and commercial sex workers, while 17.4% and 9.4% took alcohol and drugs before having sex, respectively. By logistic regression analysis, students aged 24-30 years old (an odds ratio (AOR) = 0.57, 95% confidence interval (CI) = 0.377-0.859) and faculty type (AOR = 5.69, 95% CI = 4.019-8.057) were the significant predictors for the knowledge level. Knowledge on the non-HIV causes of STDs is still lacking, and the risky behavior practiced by the sexually-active students in this study is alarming. There is a need to revisit the existing STD education curriculum in both schools and universities so that appropriate intervention on STDs can be implemented.